THE INFLUENCE OF CONSUMPTIVE BEHAVIOR ON THE USE OF SHOPEE PAYLATER MUSLIM CONSUMERS IN JABODETABEK - Lestari, Devi (Jurnal Syarikah : Jurnal Ekonomi Islam, 2025)
This study aims to determine the Effect of Consumptive Behavior on the Use of Shopee Paylater Muslim Consumers in Jabodetabek.Consumptive behavior in this study is related to tabzir, israf, and tasyabuh. This study used quantitative methods, using questionnaires as a data collection technique. This research was conducted in the Jabodetabek area or area. Data was obtained from the distribution of questionnaires as many as 100 respondents. The analysis technique used is a logistic regression analysis technique with the help of IBM SPSS version 23. The results of this study show that there is a significant influence between consumptive behavior and shopee paylater. Based on the results of the hypothesis test, the variable that greatly influences shopee paylater is the israf obtained a signification number (sig) of 0.029. This shows that there is a significant relationship in this hypothesis test because the number of significance is less than 0.05 So it can be concluded that Ha's hypothesis which states consumptive behavior affects the use of shopee paylater Muslim consumers in Jabodetabek.